Fiber Arts Require Spatial Skills: How a Stereotypically Feminine Practice Can Help Us Understand Spatial Skills and Improve Spatial Learning. - Bennett-Pierre, Grace; Gunderson, Elizabeth A. (Sex Roles, 2023)
In this review, we propose that fiber arts – a wide array of practices that use string, yarn, and fabric to create functional and fine art textiles – present a novel avenue to both explore basic science questions about spatial skills and to design interventions that help children learn spatial skills. First, we outline how fiber arts are applicable to existing theoretical frameworks that aim to organize our understanding of spatial skills and highlight how fiber arts may be particularly relevant for understanding critically understudied non-rigid spatial skills. Next, we review the environmental factors that influence spatial skill development. In the third section of the paper, we review the literature on gender differences in spatial skill performance, as well as intervention approaches that have been taken to close gender gaps. Fourth, we outline how motivational features of fiber arts, specifically the roles of individual choice in goal-setting, and growth-mindset-consistent messages in fiber arts contexts, could contribute to spatial learning. Finally, we suggest several avenues for future research, including leveraging fiber arts materials and techniques to investigate non-rigid mental transformation skills, and designing gender-inclusive fiber-arts-based spatial skills interventions that maintain the motivationally relevant features of fiber arts practices and contexts.